Food for Education in Guatemala: links between food intake and reading comprehension. Issue 7 (3rd October 2019) - Crea, Thomas M.; Diaz-Valdes, Antonia; Wang, Kaipeng; Easton, Scott D.; Urizar, Brenda
ABSTRACT: This study examined how dietary diversity and key demographics are linked to greater Spanish reading comprehension for child beneficiaries of a USDA-funded Food for Education programme in Guatemala. All students in 3rd and 6th grade were surveyed across 118 schools, 3519 children in total. Generalised linear mixed models examined the influence of dietary diversity, and K'iche' language ability, on children's Spanish reading comprehension. Dietary diversity showed no significant relationships. However, consumption of eggs on the day of assessment predicted higher reading comprehension scores. Children who indicated they spoke K'iche' fared worse on assessments. Implications for policy, practice, and research are discussed.